Factor structure of the brief psychiatric rating scale-expanded among outpatients with psychotic disorders in five Southeast European countries: evidence for five factors - Bajraktarov, Stojan; Blazhevska Stoilkovska, Biljana; Russo, Manuela; Repišti, Selman; Maric, Nadja P.; Dzubur Kulenovic, Alma; Arënliu, Aliriza; Stevovic, Lidija Injac; Novotni, Ljubisha; Ribic, Emina; Konjufca, Jon; Ristic, Ivan; et al. (Frontiers in Psychiatry, 2023)
Brief Psychiatric Rating Scale (BPRS) is a useful tool for measuring the severity of psychopathological symptoms among patients with psychosis. Many studies, predominantly in Western countries, have investigated its factor structure. This study aims: a) to further explore factor structure of the BPRS-Expanded version (BPRS-E, 24 items) among outpatients with psychotic disorders in Southeast European context; b) to confirm the identified model; and c) to investigate the goodness-of-fit of the three competing BPRS-E factor models derived in previous studies. The exploratory factor analysis produced a solution with 21 items grouped into 5 factors, thus supporting the existence of a fifth factor, i.e., Disorganization. A follow-up confirmatory factor analysis revealed 19-item model (with two items removed) that fitted the data well. In addition, the stability of two out of three competing factor models was confirmed. The BPRS-E model with 5 factors yielded in this cross-national study was found to include greater number of items in comparison to competing models.